Use of planar covariation in lower limb kinematics to characterize adaptations of running after cycling in elite triathletes - Walsh, J. A.; Stamenkovic, A.; Dawber, J. P.; Stapley, P. J. (Frontiers in Sports and Active Living, 2023)
Purpose: To characterize alterations of lower limb intersegmental coordination during the acute phase of running after cycling among highly trained triathletes using an analysis of planar covariation.